A review of shared control in automated vehicles: System evaluation - Sarabia, Joseba; Marcano, Mauricio; Pérez, Joshué; Zubizarreta, Asier; Diaz, Sergio (Frontiers in Control Engineering, 2023)
Shared control has gained considerable attention in the automated vehicle field in recent years, both from a theoretical point of view and also with multiple applications. The development of shared control systems was discussed in a previous review, which presented a taxonomy focused on control algorithms. However, it is still necessary to understand how these systems can be assessed in terms of system performance, driver behavior, cooperation, and road safety. The purpose of this paper is to review and classify evaluation methods used in recent studies with real drivers. Results of the present review showed that shared control continues to be of interest to researchers of automated vehicles. Among other changes, the methodology for system evaluation has evolved, with more participants, better testing platforms, and a greater number of comparison baselines. To guide the path toward implementing shared control features in commercial vehicles, this review aims to help researchers to perform relevant evaluation studies in future developments.